Arsenic trioxide attenuates STAT-3 activity and epithelial-mesenchymal transition through induction of SHP-1 in gastric cancer cells - Kim, Sung Ho (BMC Cancer, 2018)
BACKGROUND: We investigated the effect of arsenic trioxide (ATO) for inhibition of signal transducer and activator of transcription 3 (STAT3) and epithelial-mesenchymal transition (EMT) in gastric cancer cells, and the role of SH2 domain-containing phosphatase-1 (SHP-1) during this process. METHODS: We used AGS cells, which showed minimal SHP-1 expression and constitutive STAT3 expression. After treatment of ATO, cellular migration and invasion were assessed by using wound closure assay, Matrigel invasion assay and 3-D culture invasion assay. To validate the role of SHP-1, pervanadate, a pharmacologic phosphatase inhibitor, and SHP-1 siRNA were used. Xenograft tumors were produced, and ATO or pervanadate were administered via intraperitoneal (IP) route. RESULTS: Treatment of ATO 5 and 10 μM significantly decreased cellular migration and invasion in a dose-dependent manner. Western blot showed that ATO upregulated SHP-1 expression and downregulated STAT3 expression, and immunofluorescence showed upregulation with E-cadherin (epithelial marker) and downregulation of Snail1 (mesenchymal marker) expression by ATO treatment. Anti-migration and invasion effect and modulation of SHP-1/STAT3 axis by ATO were attenuated by pervanadate or SHP-1 siRNA. IP injection of ATO significantly decreased the xenograft tumor volume and upregulated SHP-1 expression, which were attenuated by co-IP injection of pervanadate. CONCLUSION: Our data suggest that ATO inhibits STAT3 activity and EMT process by upregulation of SHP-1 in gastric cancer cells.